Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The degree of creative leadership practice among principals of governmental basic schools in the city of Hebron from the teachers’ point of view Mrs. Hanadi Asaad Amer Asafra 2. Educational aspects in Malik Bin Nabi’s thought "An analytical study" Co-Prof. Muslim Abdul-Qadir Mudawi 3. The effect of involving the Kuwaiti labor market in developing the Public Authority for Applied Education and Training (A proposal to develop the curricula of the Mechanical Business Department) Eng. Mohammad Ahmed Mohammad Al-Awadhi 4. Strategic Planning Competences for Charter Schools Leaders in Saudi Arabia Mrs. Arwa Mohammad Abdulla Alkhwaiter, Dr.Khwater Mohammad Abdulla Alkhwaiter 5. The quality of friendship and its relationship to moral and social intelligences among students of Tafila Technical University Mrs. Rana A. Al- Ghababsheh, Prof. Ahmad M. Thawabieh 6. Development of flourishing scale among a sample of Umm Al-Qura university students Mrs. Walaa Mansour Al-Sharif , Co-Prof. Sumaya Ezzat Sharaf 7. The Predictive Ability of Social Media Addiction and Social Isolation in Loneliness Among Al-Quds Open University Students Prof. Mohammed Ahmed Shaheen, Lecturer Ilham Omar Aldeek